On the Road with Religion-and-Science and the Romance of the Past - Schweitz, Lea F. (Zygon, 2010)
Abstract. This essay responds to the question “Where Are We Going?Zygon and the Future of Religion-and-Science” and was first presented on 9 May 2009 at a symposium honoring Philip Hefner's editorship of Zygon. It offers four suggestions for the future of religion-and-science: Ask big questions; encourage cultural literacy in the public sphere; bring a critical voice to other academic disciplines; and include the history of philosophy.